Spatial and temporal drought analysis in the Krishna river basin of Maharashtra, India. Issue 1 (31st December 2016) - Mahajan, Dattatraya R.; Dodamani, Basavanand M.
Abstract: Droughts can be distinguished by three vital characteristics—spatial coverage, intensity, and duration. The objective of the present study was to study the temporal and spatial variation of drought incidences by using the Standardized Precipitation Index (SPI) and Percent of Normal Precipitation (PNP) at multiple time scales; computed using monthly precipitation data (1960–2012) in the study area of 59 rain gauge stations. Drought climatology based on these drought indices (PNP and SPI) has been studied for finding out their suitability for drought monitoring over Krishna basin in Maharashtra. Study results indicate that at dry and wet conditions, the SPI performs better than PNP in monitoring drought at multiple time scales. However, SPI-1 fails to recognize drought conditions in pre-monsoon and post-monsoon months. The spatially interpolated droughts maps are prepared which displays the variation of drought severity across the study area. The ranking of stations has been done as per drought severity to identify severely drought prone areas.